2019
DOI: 10.3390/su11205598
|View full text |Cite
|
Sign up to set email alerts
|

Does Urban Sprawl Inhibit Urban Eco-Efficiency? Empirical Studies of Super-Efficiency and Threshold Regression Models

Abstract: With rapid urbanization in China, the phenomenon of urban sprawl has become prominent and has severely challenged sustainable urbanization and ecological civilization. Aiming to understand the impact of urban sprawl on the urban environment, this study calculates the eco-efficiency of 264 prefecture-level cities in China from 2003 to 2016 by using a super-efficiency data envelopment analysis model. Then, we establish a panel Tobit model and threshold regression model to empirically test the impact of urban spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Sustainability employs urban eco-efficiency and form to determine the impact of consumption and deterioration of natural resources [9]. Stating that there may be a relationship directly between urban form and agricultural urban eco-efficiency [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainability employs urban eco-efficiency and form to determine the impact of consumption and deterioration of natural resources [9]. Stating that there may be a relationship directly between urban form and agricultural urban eco-efficiency [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Urban forms are closely related to accelerated urban population growth [12][13][14] and accessibility of natural resources [15,16] reducing open spaces [17], in order to know the sustainable situation that these urban forms are in, methods of urban development evaluation are included [14] employing density, spatial geometry, accessibility and their distance; which are better known as their urban structure [15]. A very important indicator also for urban development is eco-efficiency [10,18]; urban ecoefficiency is a tool for sustainability analysis that indicates how to perform economic activities efficiently [19]; where it applies an index of financial or beneficial result obtained with respect to the ecological or/and environmental or resource cost required by certain activities [20], collecting important data accessed by the inhabitants, these data are their input and output indicators [18], each indicator indicates the consumption made by the inhabitants [11,21] while their outputs are the emissions they may generate during or after their consumption [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis results based on a linear mixed model showed that urban sprawl has a negative impact on arthropods; in addition, the measurement of urban sprawl was analyzed and studied [10]. Zhang et al (2019) used the super-efficiency data envelopment analysis model to calculate the ecological efficiency of 264 prefecture-level cities in China. Through the empirical test of the panel model and the threshold regression model, as well as the measurement analysis of urban sprawl, the urban sprawl was found to have an influence on both the threshold effects and the ecological efficiency of city size [11].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2019) used the super-efficiency data envelopment analysis model to calculate the ecological efficiency of 264 prefecture-level cities in China. Through the empirical test of the panel model and the threshold regression model, as well as the measurement analysis of urban sprawl, the urban sprawl was found to have an influence on both the threshold effects and the ecological efficiency of city size [11]. In summary, currently, research on urban sprawl measurement is abundant, while few research results have been combined with intelligent algorithms and other means.…”
Section: Introductionmentioning
confidence: 99%